Lirasniara, the sung language of Southwest Maluku (East-Indonesia) - van Engelenhoven, Aone (UI Scholars Hub, 2010)
This paper discusses a highly endangered sung style in Maluku Barat Daya along the lines of Sasse's (1992) theory of language death and focusses on structural consequences, the speech behaviour, and the external setting of this oral tradition. It is concluded that if it really has existed and not only in local folklore, Lirasniara must have been a jargon that was replaced by Malay. Only because it already occurred in sung texts during the latter's introduction prevented its total disappearance from the region thus far. The fear remains that in the process of the modernization of Indonesia, it may undoubtedly disappear after all in the near future.